Ameliorating effect of S-2(ω-aminoalkylamino) alkylaryl sulfide (DRDE-07) on sulfur mustard analogue, 2-chloroethyl ethyl sulfide-induced oxidative stress and inflammation. (25th October 2013) - Sawale, Shekhar D.; Ambhore, Pratul D.; Pawar, Pallavi P.; Pathak, Uma; Deb, Utsab; Satpute, Ravindra M.
Abstract: Sulfur mustard (SM; 2, 2′-dichloro diethyl sulfide), an alkylating chemical warfare agent, poses a major threat in both military conflict and chemical terrorism situations. 2-chloroethyl ethyl sulfide (CEES) is a monofunctional analogue of SM, frequently used in laboratory settings, therefore increasing chances of its exposure. S-2(ω-aminoalkylamino) alkylaryl sulfide (DRDE-07) is an analogue of amifostine reported to have protective effects against SM but its effect on CEES is largely unexplored. Therefore, this study was planned to explore the effects of DRDE-07 against CEES-induced toxicity. 0.75 LD50 (1068 mg/kg) of CEES was exposed percutaneously in the presence or absence of DRDE-07 (249 mg/kg p.o.) which is given prophylactically (before 30 minute) to male mice. Animals were sacrificed on 24 h, 7th day and 14th day of CEES exposure, and tissues were collected to study oxidative stress and inflammatory markers. CEES exposure depleted intracellular GSH level and activities of GSH-linked enzymes (GR, GPx and GST) which play a major role in GSH metabolism. CEES exposure augmented lipid peroxidation indicating severe oxidative stress. It also initiated inflammation causing an increase in proinflammatory (IL1-α, IL1-β, IL-6, TNF-α and IFN-ϒ) and corresponding decrease in anti-inflammatory cytokines (IL-4 and IL-10). This was also accompanied by neutrophils infiltration indicated by higher than normal myeloperoxidase (MPO) levels. DRDE-07 efficiently reduced the oxidative stress and also facilitated to resolve inflammatory alterations. This study thus evaluated the beneficial role of DRDE-07 in ameliorating the deleterious effects of CEES and can be potentially used against SM/CEES poisoning.